Scarring the Black body : race and representation in African American literature - Henderson, Carol E., 1964- (University of Missouri Press, 2002)
"Scarring and the act of scarring are recurrent images in African American literature. In Scarring the Black Body, Carol E. Henderson analyzes the cultural and historical implications of scarring in a number of African American texts that feature the trope of the scar, including works by Sherley Anne Williams, Toni Morrison, Ann Petry, Ralph Ellison, and Richard Wright."--Jacket